PARADIGMA PENDIDIKAN ISLAM DALAM TRANSFORMASI SISTEM KEPERCAYAAN TRADISIONAL - Abdul Halik (Al-Ishlah: Jurnal Pendidikan Islam, 2016)
Islamic education encourages generations to change and maximize their potential in performing their duties as abid and caliph with a sense of responsibility. The tough person who love science born out of Islamic education, the social community will change for the better based on the demands and needs of the times.Islamic education is the process of introducing authentic and kaffah Islam to learners without necessarily negating local culture and traditions, thus accommodating and justifying local wisdom that is considered in line with Islamic teachings. Cultures and traditions are the work of humans emerging from the 'womb' of history and considered as sacred and respected things by the human. Islamic education is as a holistic education concept that accommodates all the worldviews that are 'tied' in Islamic monotheistic reason and emphasizes the human’s activities be consistently transcendent dimension and fosters creativity in realizing the mission of the caliph as the main task of making Islam as the religion of rahmatan lil alamin.